Deep integration in Latin American trade agreements - Fuentes Sosa, Ninfa M. (New York, NY : Routledge, 2022)
"Trade agreements have uncontested relevance as essential instruments governing international trade, yet little attention has been directed towards explaining differences in their content. Deep Integration in Latin American Trade Agreements analyzes the structure, nature, and characteristics of deep integration in trade agreements established by Latin American countries after the crises of 1982 and until 2020 with their regional and extra-regional partners. Ninfa M. Fuentes Sosa argues that deep integration can be disaggregated into its institutional, operative, and horizontal dimensions (which differ regarding their functions and application level). Empirically, she demonstrates that trade provisions can be mapped, measured, and allocated into their corresponding dimension, providing an understanding of the deep integration structure in Latin America. She claims that the current structure poses challenges for deepening regionalism at a broad scale. Countries working on specific areas over time could diminish obstacles that have prevented them from achieving deeper trade integration. Providing an operational definition and measures of deep integration, this book will be of great interest to scholars, graduate students, and policymakers working in the field of international political economy, trade and trade politics"--
Keywords: Latin America -- Commercial treaties; Latin America -- Economic conditions -- 1982-; POLITICAL SCIENCE / International Relations / Trade & Tariffs